Barcoding helps threatened species: the case of Iris marsica (Iridaceae) from the protected areas of the Abruzzo (Central Italy). (1st November 2020) - De Castro, O.; Del Guacchio, E.; Di Iorio, E.; Di Maio, A.; Di Martino, L.; Bartolucci, F.; Conti, F.
Abstract: Aiming at clarifying the discussed distribution of Iris marsica, endemic to central Italy, the authors tested the application of molecular techniques for the correct identification of this taxon, especially towards the similar, non-native I. × germanica . In fact, it was suspected that their morphological similarity would cause misidentification in the past, causing uncertainty of distributional data and consequently a weakening of conservation measures for I. marsica . After a comparison with the topotypical population of I. marsica, the authors found that DNA barcoding based on plastid sequences and nuclear microsatellites markers represents an effective identification tool, perfectly congruent with the preliminary morphological analyses and the chromosome counts. According to the results and despite some recent indications, I. marsica actually occurs also outside the National Park of Abruzzo, Lazio and Molise (central Italy), in further protected areas.